2019
DOI: 10.1097/md.0000000000013951
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic bacterial airway infection and prognosis of bronchiolitis obliterans syndrome after hematopoietic cell transplantation

Abstract: Bronchiolitis obliterans syndrome (BOS) is a rare pulmonary complication of hematopoietic stem cell transplantation (HSCT) with high mortality. Chronic bacterial airway infection (CAI) causes exacerbation and progression of several airway diseases, and bacterial airway colonization was shown to be associated with BOS after lung transplantation.We assessed the association between CAI and clinical course in patients with BOS after HSCT. This retrospective study included 910 patients undergoing allogeneic HSCT be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Similar to a recent study, we demonstrated that pro-inflammatory macrophages induced fibroblast activation [39]. BOS patients have shown a high incidence of bacterial infection, described as a source of lipopolysaccharide [40] and interferon-γ [41], that together could promote macrophage differentiation towards a pro-inflammatory phenotype in BOS. In vitro inhibition of CatB activity resulted in the prevention of fibroblast activation.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to a recent study, we demonstrated that pro-inflammatory macrophages induced fibroblast activation [39]. BOS patients have shown a high incidence of bacterial infection, described as a source of lipopolysaccharide [40] and interferon-γ [41], that together could promote macrophage differentiation towards a pro-inflammatory phenotype in BOS. In vitro inhibition of CatB activity resulted in the prevention of fibroblast activation.…”
Section: Discussionsupporting
confidence: 90%
“…27 The cur rent inci dence is approx i ma tely 3% in pedi at ric and 3% to 6% in adult HCT. 1,[51][52][53] A chal lenge of this dis ease has been its insid i ous nature lead ing to mod er ate decline at diag no sis. The fre quent use of home devices to detect early de clines in lung func tion and the use of FEF25-75 as an indi ca tor may aid in the ear lier iden ti fi ca tion of BOS.…”
Section: Bronchiolitis Obliterans Syn Dromementioning
confidence: 99%
“…18,35 In our cohort, all patients with BOS suffered from an acute or chronic GvHD of at least one organ site. Furthermore, we revealed that the mortality was significantly higher when three organ sites were affected by GvHD ( busulfan-based conditioning regimen, unrelated donor, gastroesophageal reflux disease, acute or chronic viral, and bacterial infections, 13,34,36 were investigated and displayed in Table 3. Seven patients suffered from infections after aHSCT, four patients received a busulfanbased conditioning regime, and four patients had an unrelated donor.…”
Section: Discussionmentioning
confidence: 99%